2008
DOI: 10.1093/humrep/den098
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of ESR1 and ESR2 that may influence estrogen activity and the risk of hypospadias

Abstract: These findings suggest that the G allele containing variants of ESR1 XbaI and the G allele containing variants of ESR2 2681-4A>G may decrease the risk of hypospadias, whereas the ESR1 C-A haplotype may increase its risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 21 publications
0
34
0
2
Order By: Relevance
“…Previously, polymorphic ESR2 variants have been associated with milder variations in sexual development such as hypospadias and micropenis, [25][26][27][28][29] and a heterozygous ESR2 variant c.1295C > A leading to a missense change p.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, polymorphic ESR2 variants have been associated with milder variations in sexual development such as hypospadias and micropenis, [25][26][27][28][29] and a heterozygous ESR2 variant c.1295C > A leading to a missense change p.…”
Section: Discussionmentioning
confidence: 99%
“…The AGAGA haplotype of the estrogen receptor 1 (ESR1) gene is strongly associated with hypospadias [117]. The ESR1 C-A haplotype, for ESR1 XbaI and ESR2 2681-4A>G, respectively, increases the risk of malformation, as well [118]. An increased number of CA repeats (and subsequently increased ER activity) also augments the risk of malformation [119], and more recently we identified ATF3 polymorphisms in patients with isolated hypospadias [120].…”
Section: Iii-2-2 Gene Polymorphismsmentioning
confidence: 90%
“…[13][14] Both our study, and other previous studies have identified that genetic variants for ESR1 and ESR2 could raise the susceptibility of CO and HS by enhancing the effects of estrogenic EEDs, which are known as xenoestrogens and currently the largest group of known EEDs. 7,15 In addition, several nuclear receptors, such as aryl-hydrocarbon receptor (AHR) and pregnane X receptor (PXR or NR1I2), are known to be crucial for EED-mediated CYP transcription. 16 Previous studies have reported that polymorphisms in AHR may affect AHR functions, notably the induction of CYP1 genes, suggesting a potential role for nuclear receptor polymorphisms in the variable responses to xenobiotic chemicals.…”
Section: Introductionmentioning
confidence: 99%